The Relationships among 5S Activities and 7 Methods of Waste Reduction in the Production Process at a Sugar Factory in the Northeastern Area of Thailand: ความสัมพันธ์ระหว่างกิจกรรม 5ส กับการลดความสูญเปล่า 7 ประการ ในกระบวนการผลิตของโรงงานน้ำตาลในเขตภาคตะวันออกเฉียงเหนือของประเทศไทย - Kijjadhip, Tanarut; Rojniruttikul, Nuttawut (Journal of Applied Economics and Management Strategy, 2019)
บทคัดย่อ วัตถุประสงค์ของการวิจัยนี้คือ 1) เพื่อศึกษาระดับกิจกรรม 5ส ในกระบวนการผลิตของโรงงานน้ำตาลเขตภาคตะวันออกเฉียงเหนือของประเทศไทย 2) เพื่อศึกษาระดับการลดความสูญเปล่าในกระบวนการการผลิตของโรงงานน้ำตาลเขตภาคตะวันออกเฉียงเหนือของประเทศไทย และ 3) เพื่อศึกษาความสัมพันธ์ระหว่างกิจกรรม 5ส กับการลดความสูญเปล่าในกระบวนการผลิตของโรงงานน้ำตาลเขตภาคตะวันออกเฉียงเหนือของประเทศไทย กลุ่มตัวอย่างที่ใช้ในงานวิจัย คือ พนักงานฝ่ายผลิตของโรงงานน้ำตาลในเขตภาคตะวันออกเฉียงเหนือจำนวน 107 คน เครื่องมือที่ใช้ในการวิจัย คือ แบบสอบถาม สถิติที่ใช้ในการวิจัย ได้แก่ ค่าร้อยละ ค่าเฉลี่ยเลขคณิต ส่วนเบี่ยงเบนมาตรฐาน และการทดสอบสมมติฐานด้วยการวิเคราะห์สหสัมพันธ์ของเพียร์สัน ผลการวิจัยพบว่า 1) ระดับของการทำกิจกรรม 5ส ในกระบวนการผลิตของโรงงานน้ำตาลเขตภาคตะวันออกเฉียงเหนืออยู่ในระดับมาก 2) ระดับการลดความสูญเปล่าในกระบวนการผลิตของโรงงานน้ำตาลเขตภาคตะวันออกเฉียงเหนืออยู่ในระดับมาก และ 3) กิจกรรม 5ส มีความสัมพันธ์ต่อระดับการลดความสูญเปล่าในทิศทางเดียวกัน อย่างมีนัยสาคัญทางสถิติที่ระดับ 0.01 ในระดับมาก คำสำคัญ: กิจกรรม 5ส การลดความสูญเปล่า โรงงานน้ำตาล กระบวนการผลิต ABSTRACT The objectives of this research were: 1) to study the level of 5S activities in the production process of sugar factories in the northeastern part of Thailand 2) to study the level of waste reduction in the production process of sugar factories in this area; and 3) to study the relationships among 5S activities and the waste reduction in the production process of the sugar factories in that area. The sample size was 146 production staff members in the sugar factories and questionnaires were used as the research instrument. The statistics included percentage, arithmetic mean, and standard deviation; and Pearson correlation were used for the hypothesis testing. The research results showed that the 5S activities in the production process at a sugar factory in the northeastern area were at a high level. Secondly, the waste reduction in the production process at a sugar factory in the northeastern area was also at a high level. Lastly, the 5S activities were related to the waste reduction process at a statistical significance level of 0.01. Keywords: 5S Activities, Waste Reduction, Sugar Factory, Production Process